TRANSFORMATION OF CORPORATE CULTURE UNDER THE INFLUENCE OF GLOBALIZATION PROCESSES - Tojieva Shakhnoza Bobomuratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This scientific paper analyzes the impact of globalization and digitalization processes on the transformation of corporate culture. The study examines changes in corporate culture at the technological, social, and value-based levels, as well as their influence on organizational performance, human capital, and management systems. Special attention is given to the glocal management model, which ensures a balance between national values and global standards. The research findings demonstrate the necessity of developing innovative thinking, transparency, inclusiveness, and digital competencies within the corporate environment.